Ecofriendly Route for the Synthesis of Highly Conductive Graphene Using Extremophiles for Green Electronics and Bioscience. (9th April 2013) - Raveendran, Sreejith; Chauhan, Neha; Nakajima, Yoshikata; Toshiaki, Higashi; Kurosu, Shunji; Tanizawa, Yuji; Tero, Ryugo; Yoshida, Yasuhiko; Hanajiri, Tatsuro; Maekawa, Toru; Ajayan, Pulickel. M.; Sandhu, Adarsh; et al.
<x xml:space="preserve">Abstract</x> Highly conductive biocompatible graphene is synthesized using ecofriendly reduction of graphene oxide (GO). Two strains of non‐pathogenic extremophilic bacteria are used for reducing GO under both aerobic and anaerobic conditions. Degree of reduction and quality of bacterially reduced graphene oxide (BRGO) are monitored using UV–vis spectroscopy, X‐ray photoelectron spectroscopy, and Raman spectroscopy. Structural morphology and variation in thickness are characterized using electron microscopy and atomic force microscopy, respectively. Electrical measurements by three‐probe method reveal that the conductivity has increased by 104–105 fold from GO to BRGO. Biocompatibility assay using mouse fibroblast cell line shows that BRGO is non‐cytotoxic and has a tendency to support as well as enhance the cell growth under laboratory conditions. Hereby, a cost effective, non‐toxic bulk reduction of GO to biocompatible graphene for green electronics and bioscience application is achieved using halophilic extremophiles for the first time.